Adaptive Network Fuzzy Inference System (ANFIS) Handoff Algorithm - Kwong, Chiew Foong; Chuah, Teong Chee; Lee, Sze Wei (IEEE, 2009)
Mobility management in the heterogeneous environment demands different design approach, especially in the handoff decision. This is to fulfill the different requirements of different segments especially in the hybrid satellite and terrestrial scenario. There are many works done to replace the traditional handoff algorithm such as hysteresis and fuzzy logic based handoff algorithm. The fuzzy handoff algorithm proposed by earlier work is not optimized and required constant attention from the human experts. This paper proposes a newer approach using Adaptive Network Fuzzy Inference System (ANFIS) where the training element is incorporated into the existing fuzzy handoff algorithm.